Dynamized Aloysia Polystachya (Griseb.) Essential Oil: A Promising Antimicrobial Product - Nader, Talita Thomaz; Leonel, Alexandre Henrique; Henrique, Camila Yamasita; Contini, Silvia Helena Taleb; Crevelin, Eduardo José; França, Suzelei de Castro; Berton, Bianca Waléria; Pereira, Ana Maria Soares (Homeopathy, 2022)
Background Compounds from vegetal matter have therapeutic potential to control highly prevalent microorganisms that are resistant to commonly used antimicrobial drugs. Dynamization of compounds can either maintain or improve their therapeutic effects, and make their use safer, especially those compounds whose therapeutic dose is close to the toxic limit. Aloysia polystachya (Griseb.) stands out among aromatic plants with antimicrobial potential.Objective The aim of this study was to evaluate the antimicrobial activity of dynamized and crude forms of A. polystachya essential oil against Candida albicans, Escherichia coli and Staphylococcus aureus.Methods Essential oil was extracted from A. polystachya dry leaves, solubilized, and dynamized at 1 cH potency as recommended by the Brazilian Homeopathic Pharmacopoeia. Antimicrobial activity against C. albicans, E. coli and S. aureus of the samples was assayed using the plate microdilution method.Results Dynamized A. polystachya essential oil at the concentration of 1 μg/mL inhibited the growth of all the microbial species analyzed. The minimum inhibitory concentration of dynamized essential oil was smaller than crude essential oil for S. aureus, E. coli and C. albicans.Conclusion It is reported for the first time that A. polystachya dynamized essential oil can effectively suppress microbial growth, and it is a promising adjuvant to treat infections with pathogenic S. aureus, E. coli and C. albicans.
Keywords: Aloysia polystachya; essential oil; dynamization; antibacterial activity; antifungal activity